Standarization Of Pinyaram Banana Recipesasa Traditional Cakes In Kenagarian Salayo Solok Regency - Amalia, Anisa; Gusnita, Wiwik (Universitas Negeri Padang, 2023)
This study aims to standardize the banana pinyaram recipe in Kanagarian Salayo, Solok Regency which includes shape, color, aroma, texture and taste. This research was conducted to standardize the banana pinyaram recipe in Kenagarian Salayo which includes: ingredients, amount of ingredients, method of making, and quality.The type of research used is the mixed method (Mixed Method), which is a combination of quantitative and qualitative methods. direct experiment on the manufacture of banana pinyaram. The qualitative method is to make observations by interviewing the informants. This research was conducted in four jorongs in Kanagarian Salayo, Kubung District, Solok Regency and Workshop the Catering. This qualitative study used a completely randomized design (CRD) with 3 repetitions. The primary data used was obtained directly from 3 expert panelists who gave answers to the organoleptic test format for the standardized quality of banana pinyaram in Kanagarian Salayo, Solok Regency, which was then tabulated into a table form and analyzed to see the differences between the 10 recipes that would be standardized by the t test. Qualitative research is to make observations by interviewing the informants. The results showed the average value of shape (neat semi-circle) 3.67, color (dark brown) 3.89, aroma (scented banana) 3.56, texture (chewy) 3.67 and taste (sweet) 3.33.